Enhanced Dissolution of Naproxen by Combining Cocrystallization and Eutectic Formation - Hakyeong Kim; Soeun Jang; Il Won Kim (MDPI AG, 2021)
Improving dissolution properties of active pharmaceutical ingredients (APIs) is a critical step in drug development with the increasing occurrence of sparingly soluble APIs. Cocrystal formation is one of the methods to alter the physicochemical properties of APIs, but its dissolution behavior in biorelevant media has been scrutinized only in recent years. We investigated the combined strategy of cocrystallization and eutectic formation in this regard and utilized the cocrystal model system of naproxen and three pyridinecarboxamide isomers. Binary melting diagrams were constructed to discover the eutectic compositions of the three cocrystals with excess amounts of pyridinecarboxamides. The melt-crystallized eutectics and cocrystals were compared in their dissolution behaviors with respect to neat naproxen. The eutectics enhanced the early dissolution rates of the cocrystals in both the absence and presence of biologically relevant bile salt and phospholipid components, whereas the cocrystal dissolution was expedited and delayed, respectively. The combined strategy in the present study will be advantageous in maximizing the utility of the pharmaceutical cocrystals.